DIPLOMASI KEBUDAYAAN INDONESIA TERHADAP SPANYOL MELALUI KULINER TAHUN 2012-2015 - Siregar, Nur Jannah; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explain about Indonesia was using Culinary as a tool of diplomacy to Spain in 2012-2015. Cultural diplomacy using this culinary starting from gastronomy week events held republic Indonesian embassy in Spain precisely on 22 January 2012 to invite some ambassadors to taste the Indonesia’s culinary. Indonesian gastronomy week is the result of cooperation Embassy in Madrid, the Ministry of Tourism and Creative Economy, Intercontinental Madrid and Mid Plaza Jakarta in the Restaurant Intercontinental Madrid, Spain.By using the theory of cultural diplomacy, the next will be presented also the culinary owned by Indonesia and Spain as well as the similarity thus becoming one of the considerations of cultural diplomacy using this culinary untill today. Indonesian ambassador to Spain also explained that they will consistently promote Indonesian culture in Spain mainly through culinary. This is a qualitative research by conducting literature rewiew and compiling data from journals, book, and websites.This research shows how the efforts of Indonesia to increase cooperation with Spain through cultural diplomacy. One is to use a culinary as well as holding events such as Gastronomy Week on 2012 and Culinary Heritage Week Indonesia on 2015.Keywords: Culinary, Cultural Diplomacy, Indonesia-Spain Relations